Comments on the nomenclatural status of two subgeneric names for marine gastrotrichs (Gastrotricha: Xenotrichulidae) - Abukawa, Shushi; Kajihara, Hiroshi (Zootaxa, 2011)
Remane (1927) established the generic name Xenotrichula for a single species of marine gastrotrich, Xenotrichula velox Remane, 1927. Recently, Hummon and Todaro (2010: 22–23) created the new subgenus Velox, designating X. velox as the type species, despite Article 44.1 of the International Code of Zoological Nomenclature (hereafter, the "Code") (ICZN 1999). Because the subgeneric names Xenotrichula Remane, 1927 and Velox Hummon & Todaro, 2010 share the same name-bearing type species, the latter is an objective junior synonym of the former and thus should be regarded as permanently invalid. Hence the nominotypical subgenus must be expressed as Xenotrichula (Xenotrichula) Remane, 1927, and its type species Xenotrichula (Xenotrichula) velox.